Edukasi Sapta Pesona Dan Peduli Lingkungan Pada Anak-Anak Sekolah Dasar Daerah Pesisir - Lina Eta Safitri; Putri Adekayanti; Nurlaila Agustikawati (Pusat Riset dan Inovasi Nasional, 2023)
The potential for natural resources that are widespread on the coasts of Indonesia, the potential for pollution of the coastal and marine environment also has considerable opportunities. This opportunity can be caused by Indonesia's dense population, relatively high tourist activity including transportation, and large development. For this reason, the purpose of this community service activity is to foster awareness and increase elementary school children's understanding of the importance of caring for the environment and sapta charm. This community service activity is educational in nature by dividing small groups, where the children of SD Negeri Empan are directly taught about Sapta Pesona and caring for the environment and practice the waste sorting process directly. The expected result is the understanding of SD Negeri Empan children about Sapta Pesona and caring for the environment. Community service activities can then be directed to the practice of how to manage and carry out waste recycling and the symbolic installation of eight Sapta Pesona points in coastal environments, especially tourist attractions